Probing athletics tracks degradation using a microscratch technique. (September 2020) - Andena, Luca; Tagliabue, Stefano; Pavan, Andrea; Marenghi, Andrea; Testa, Manuel; Frassine, Roberto
Abstract: Continuous outdoor exposure of athletics tracks can lead to an important degradation of their mechanical and aesthetical properties. In this work, flat laboratory samples prepared from rubber blends of different colours were subjected to natural and artificial ageing, to investigate their effect on the surface properties. Compositional variations demonstrated a generalized oxidization of the outer (top) material layer, together with surfacing of inorganic additives; a small increase of the degradation temperature of the natural rubber component was reported, similar to the one previously observed on bulk track samples. The smooth surface of the present samples allowed their testing using a microscratching technique, able to mechanically probe the material within a few hundred microns below the top surface. The formation of a significantly harder outer crust layer was reported, potentially impacting the track performance since it is exactly the locus of interaction between the athlete and the sport surface. In particular, the increase in scratch hardness is accompanied by a significant reduction in the apparent friction coefficient. These surface modifications, previously unreported in the literature, are independent phenomena with respect to generalized bulk ageing. Microscratch data supported by microscopy evidenced a significantly varying sensitivity to ageing for the different colours (red, blue, green, neutral). Moreover, this sensitivity appeared strongly dependent on the applied ageing protocol (natural vs. artificial). In view of these results, care must be taken when accelerated artificial weathering is used to simulate long-term natural ageing of these materials. Highlights: Microscratching was successfully used to mechanically probe aged surfaces. The formation of a hard crust on the exposed track surface was reported. Crust hardness and thickness vary greatly depending on track colour. Colour sensitivity varies according to ageing type (natural vs. artificial). Hardness increase was also accompanied by a reduction in friction.